Unmasking the Veiled: A Comprehensive Examination of Benami Transactions and Strategies for Combating Financial Fraud - Sharma, Vishal (Journal of Global Economy, Business and Finance, 2025)
This article presents a thorough and incisive analysis of benami transactions, an intricate and often enigmatic manifestation of financial deceit that permeates numerous nations. Benami transactions entail the acquisition of assets or properties through pseudonymous identities or intermediaries, orchestrated with the intent of obfuscating true ownership. Delving into the rationales underpinning the proliferation of such transactions, their ramifications on economic dynamics are probed alongside an exploration of the diverse legal frameworks across jurisdictions devised to counteract these fraudulent ploys. Additionally, this study navigates the challenges inherent in exposing benami transactions, while proffering potential remedies to fortify regulatory infrastructures and bolster the efficacy of enforcement mechanisms.